Model for invasion of human tissue culture cells by Neisseria gonorrhoeae. - Shaw, J H (1988)
A tissue culture model has been developed for studying the ability of Neisseria gonorrhoeae to invade eucaryotic cells. The cell line HecIB, a human adenocarcinoma endometrial cell line, was found to support gonococcal invasion. The bactericidal antibiotic gentamicin was used to kill those bacteria that had not entered the HecIB cells, allowing us to quantitate internalized bacteria. Kinetic studies showed an increase in the titer of gentamicin-protected gonococci at 4 h postinfection followed by a decrease; a second increase occurred after 6 h. The state of piliation did not affect the degree of invasion when the bacteria were spun down onto the monolayer. Gonococcal invasion was inhibited when the HecIB cells were preincubated with cytochalasin D before bacterial infection. N. lactamica was used as a negative control. No internalized N. lactamica cells were observed by electron microscopy. Electron microscopy documented the intracellular location of the gonococci in HecIB cells and the eventual destruction of the invaded HecIB cells. After 24 h, clusters of gonococci encased in a matrix of cell debris were observed.